2020
DOI: 10.1097/mbp.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between blood pressure readings using a mercury versus an aneroid sphygmomanometer

Abstract: Objective For more than a century since its introduction, mercury sphygmomanometer (HgS) had been the mainstay for office measurement of blood pressure (BP). In light of the environmental and health hazards associated with mercury, there is a need to replace it with mercury-free alternatives all over the world. We aimed to validate the widely used aneroid sphygmomanometer (AnS) by comparing its BP readings against BP readings taken with an HgS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Rinfret et al (2017) showed an average systolic blood pressure difference of 4.3 mmHg between two devices, also investigated in adults (Rinfret et al, 2017). Both studies with statistically significant differences demonstrated higher correlations, up to r = 0.989 and r = 0.919, between devices compared to our study (Farhan et al, 2020; Rinfret et al, 2017). One reason why the correlation coefficient is lower in our study compared to previously reported results in adults might be the age of the investigated populations and the fact that measurements took place in the school setting.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Rinfret et al (2017) showed an average systolic blood pressure difference of 4.3 mmHg between two devices, also investigated in adults (Rinfret et al, 2017). Both studies with statistically significant differences demonstrated higher correlations, up to r = 0.989 and r = 0.919, between devices compared to our study (Farhan et al, 2020; Rinfret et al, 2017). One reason why the correlation coefficient is lower in our study compared to previously reported results in adults might be the age of the investigated populations and the fact that measurements took place in the school setting.…”
Section: Discussioncontrasting
confidence: 54%
“…Blood pressure, MAP and HR in school children did not differ between both devices. In the literature, other comparisons of blood pressure devices showed significant differences (Farhan et al, 2020;Rinfret et al, 2017). Farhan et al (2020) reported mean differences between two devices of 2.8 mmHg systolic and 2.4 mmHg diastolic blood pressure in adults (Farhan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation